Methodology for Assessing the Degree of Internationalization of Business Academic Study Programmes - Dan-Cristian Dabija; Cătălin Postelnicu; Nicolae Al. Pop (Amfiteatru Economic)
The purpose of this paper is to develop a methodology for assessing the degree of internationalization of undergraduate, Master’s and doctoral business programmes with the aid of complex indicators designed to capture the vast array of characteristics displayed by these programmes and contribute to their promotion in the international academic competition. The methodology should include both general indicators applicable to any study programme and some indicators that are specifically developed for business study programmes. No consensus exists in the internationalization literature and practice over the actual scope and the indicators to be considered in the implementation of such a study. Researchers rather propose methods for assessing and prioritizing universities and/or faculties and lay down a lot of criteria according to which rankings are developed. These rankings are mainly focused on the level of internationalization of socioeconomic and engineering study programmes. Being aware of the limits of theory and practice, the authors develop a scoring model that measures the degree of internationalization of business education curricula according to stringent criteria. The research originality lies in the attempt to describe the avenues of a new methodology for measuring and assessing realistically the economic study programmes so that these may be better positioned on the educational market and become more attractive to the future candidates. Based on a synergistic approach to indicators, the model may contribute to creating competitive advantage in relation to other programmes from the same university or from partner institutions.